Biometric Identification via Through-Wall Radar: A Survey on Vital Signs and Gait Analysis - Andre Rouco; Carolina Gouveia; Daniel Albuquerque; Susana Bras; Pedro Pinho (IEEE Access, 2025)
Advancements in radar technologies, including Continuous Wave, Frequency Modulated Continuous Wave, and Ultra-Wideband, are surveyed for their applications in biometric identification and Through-Wall Imaging. This survey focuses on radar technologies used for vital signal detection and gait analysis. A comparison of key parameters across diverse research studies is conducted. Moreover, the benefits of varying radar technologies and Artificial Intelligence algorithms are discussed. The study provides a roadmap for subsequent investigations in the fields of radar technology and biometric identification.